Class I HDACs control a JIP1-dependent pathway for kinesin-microtubule binding in cardiomyocytes. (November 2017) - Blakeslee, Weston W.; Lin, Ying-Hsi; Stratton, Matthew S.; Tatman, Philip D.; Hu, Tianjing; Ferguson, Bradley S.; McKinsey, Timothy A.
Abstract: Class I histone deacetylase (HDAC) inhibitors block hypertrophy and fibrosis of the heart by suppressing pathological signaling and gene expression programs in cardiac myocytes and fibroblasts. The impact of HDAC inhibition in unstressed cardiac cells remains poorly understood. Here, we demonstrate that treatment of cultured cardiomyocytes with small molecule HDAC inhibitors leads to dramatic induction of c-Jun amino-terminal kinase (JNK)-interacting protein-1 (JIP1) mRNA and protein expression. In contrast to prior findings, elevated levels of endogenous JIP1 in cardiomyocytes failed to significantly alter JNK signaling or cardiomyocyte hypertrophy. Instead, HDAC inhibitor-mediated induction of JIP1 was required to stimulate expression of the kinesin heavy chain family member, KIF5A. We provide evidence for an HDAC-dependent regulatory circuit that promotes formation of JIP1:KIF5A:microtubule complexes that regulate intracellular transport of cargo such as autophagosomes. These findings define a novel role for class I HDACs in the control of the JIP1/kinesin axis in cardiomyocytes, and suggest that HDAC inhibitors could be used to alter microtubule transport in the heart. Highlights: HDAC inhibitors stimulate JIP1 expression in cardiomyocytes. HDAC inhibitors stimulate KIF5A expression via JIP1 in cardiomyocytes. JIP1 alters autophagy in cardiomyocytes. A novel pathway for microtubule transport in cardiomyocytes